2024
DOI: 10.1186/s12886-024-03467-w
|View full text |Cite
|
Sign up to set email alerts
|

Refraction and ocular biometric parameters in 3-to 6-year-old preschool children : a large-scale population-based study in Chengdu, China

Jingyu Mu,
Zengrui Zhang,
Xiaoxiao Wu
et al.

Abstract: Purpose To understand the ocular biometric parameters characteristics and refractive errors in 3-to 6-year-old preschool children in Chengdu, China, and to investigate the prevalence of refractive errors. Method A school-based cross-sectional study was conducted in Chengdu from 2020 to2022 with a total of 666 kindergartens. All children were measured by non-cycloplegic autorefraction and uncorrected visual acuity (UCVA) and ocular biometric paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(50 reference statements)
1
1
0
Order By: Relevance
“…The mean AL/CR ratio was 2.86 ± 0.07, which was similar to that reported in Shenzhen [23] and Chengdu [11]. The ALs of the males and females were 22.47 ± 0.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean AL/CR ratio was 2.86 ± 0.07, which was similar to that reported in Shenzhen [23] and Chengdu [11]. The ALs of the males and females were 22.47 ± 0.…”
Section: Discussionsupporting
confidence: 85%
“…With the development of children's bodies, they exhibit varying degrees of changes in ocular biometric parameters [11]. One study showed that ocular biometric parameters are potential biomarkers for assessing myopia in children and adolescents [12].…”
Section: Introductionmentioning
confidence: 99%